Analysis of gender- and age-stratified asthma burden: forecasting prevalence trends in 2030 - Pan, Zhenzhen; Yang, Hongye; Jin, Yuting; Zhou, Qin; Wang, Qian; Hao, Chuangli; Li, Ling (Frontiers in Medicine, 2025)
BackgroundAsthma poses a global health challenge, requiring an understanding of its burden to guide policy. Using GBD 2021 data, this study aims to assess the burden of asthma worldwide.MethodsWe extracted data on asthma prevalence, incidence, years lived with disability (YLDs), and disability-adjusted life-years (DALYs) from GBD for the period 1990–2021. Age-standardized rates (ASR) and estimated annual percentage changes (EAPC) were calculated to understand trends. We analyzed variations in asthma burden across gender and age groups, and explored the correlation between socio-demographic index (SDI) and asthma burden. Furthermore, we examined the main risk factors contributing to asthma. Lastly, we predicted the future asthma burden over the next 8 years.ResultsHigh population countries such as India and China reported higher numbers of prevalence, incidence, and YLDs. From 1990 to 2021, the ASR of prevalence, incidence, and YLDs for asthma showed an overall downward trend. Children under 14 years of age demonstrated notably higher incidence rates, with the highest concentrations observed among those below 5 years, whereas the elderly population (>90 years) exhibited the peak prevalence and disability-adjusted life years (DALYs) burden. Gender differences were observed, with males having a higher burden before age 15–19, and females afterward. In China, smoking emerged as a significant risk factor for men, while the risk associated with high body mass index (BMI) has increased notably in recent years. Both incidence and prevalence in China are projected to decrease in the future.ConclusionThis study finds 15–19 years is a key turning point for gender differences in asthma burden, pinpointing smoking, high BMI, and NO₂ as risk factors. From 2022–2030, asthma prevalence/incidence is set to decline overall but rise in 15–19-year-olds, highlighting adolescence as a new prevention focus and a call for better health education in China.